Evaluation of faba beans for resistance to sclerotinia stem rot caused by Sclerotinia trifoliorum - Lithourgidis, Anastasios; Roupakias, Dimitrios; Damalas, Christos (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2004)
Sclerotinia stem rot, a fungal disease caused by Sclerotinia trifoliorum, is often a serious problem in faba beans (Vicia faba). The levels of resistance to sclerotinia stem rot were evaluated in 23 faba bean cultivars originating from various European countries, 18 cultivars from ICARDA, five cultivars from Canada, 58 populations originating from various provinces of Greece, and five V. narbonensis populations. Evaluation was done under controlled conditions following artificial inoculation with carrot root pieces colonized by the fungus. Faba bean plants were scored for resistance on a 0 to 3 severity scale. There was significant variability for resistance to S. trifoliorum among faba bean cultivars and among populations. Seven cultivars and 15 Greek faba bean populations showed a satisfactory level of resistance (≤ 1.50), whereas 22 cultivars and 25 populations were susceptible (> 2.00). However, all V. narbonensis populations were resistant to S. trifoliorum (disease severity from 1.11 to 1.44) without significant variability within populations. Variability in the resistance of faba beans to S. trifoliorum would allow selection within appropriate genotypes for breeding in an effort to provide an effective alternative for sclerotinia stem rot management in this crop.